Timeless : a century of iconic looks : recreate the classic make-up and hair styles from 100 years of beauty /: a century of iconic looks : recreate the classic make-up and hair styles from 100 years of beauty. (2017) - (Makeup artist), Young, Louise; Sheppard, Loulia
No abstract available